The Customer Journey of the Premium Traveler : Highlights of an investigation among 2.175 international travelers from the US, the UK and Spain - Gieschen, Jörn (IE University, 2018)
All stakeholders of this research, the research team and ini9ators at IE, our partners at Google Travel, Mastercard, and many industry partners, have been so excited about this research from the start due to one key reason: this research profoundly taps into a big black box, an area with many assumptions and myths, but few data and intelligence. How are premium travelers really different from their mass market peers, how do their preferences and behavioral patterns compare?To answer the many unanswered questions, a broad primary market research was undertaken in three big international markets, the US, the UK, and Spain. Over 2,100 travelers went through an extensive online questionnaire, nearly 1,500 of them fulfilled the criteria as premium travelers frequently using luxury accommodation like 5-star Grand or Boutique hotels or high-end holiday rentals, allowing to build an incredibly rich data set to explore. Clearly, the vast majority of these travelers represent the upper but not the very high-end segments of the market represented by High Networth or even Ultra High Networth individuals, reason why we rather speak of premium than of luxury market segments.So, what are the key differences between premium and standard travelers the research could unveil?
Keywords: Branding tourism agencies; Tourism agencies; Strategy; Marketing; Innovation; Luxury; Agencias turísticas; Gestión de marca; Publicidad; Premium Travels; Viajes Premium; Lujo